Developmental biology and potential use of Alboglossiphonia lata (Annelida: Hirudinea) as an “Evo-Devo” model organism - Medina Jiménez, Brenda Irene (Front Zool, 2017)
BACKGROUND: The need for the adaptation of species of annelids as “Evo-Devo” model organisms of the superphylum Lophotrochozoa to refine the understanding of the phylogenetic relationships between bilaterian organisms, has promoted an increase in the studies dealing with embryonic development among related species such as leeches from the Glossiphoniidae family. The present study aims to describe the embryogenesis of Alboglossiphonia lata (Oka, 1910), a freshwater glossiphoniid leech, chiefly distributed in East Asia, and validate standard molecular biology techniques to support the use of this species as an additional model for “Evo-Devo” studies. RESULTS: A. lata undergoes direct development, and follows the highly conserved clitellate annelid mode of spiral cleavage development; the duration from the egg laying to the juvenile stage is ~7.5 days, and it is iteroparous, indicating that it feeds and deposits eggs again after the first round of brooding, as described in several other glossiphoniid leech species studied to date. The embryos hatch only after complete organ development and proboscis retraction, which has not yet been observed in other glossiphoniid genera. The phylogenetic position of A. lata within the Glossiphoniidae family has been confirmed using cytochrome c oxidase subunit 1 (CO1) sequencing. Lineage tracer injections confirmed the fates of the presumptive meso- and ectodermal precursors, and immunostaining showed the formation of the ventral nerve system during later stages of development. Further, the spatiotemporal expression of an EF-hand calcium-binding protein Calsensin ortholog was characterized, which showed a specific pattern in both the ventral and peripheral nervous systems during the later stages. CONCLUSIONS: Our description of the embryonic development of A. lata under laboratory conditions provides new data for further comparative studies with other leech and lophotrochozoa model organisms. Moreover, it offers a basis for the establishment of this species as a model for future “Evo-Devo” studies. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12983-017-0240-y) contains supplementary material, which is available to authorized users.